Utilization of green shellfish (perna viridis) waste as an alternative material for brick production in sustainable construction - Indra Setiawan; Dea Elsa; Davina Fitria Ramadhan; Zarrar Maulidar Mardani; Andreansyah; Muhammad Lutfi Zaelani (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2025)
Based on initial observations, information from green clam shell collectors that the production of green clams in Kampung Kerang Hijau, Cilincing, North Jakarta, can reach 5 tons/day when the condition of the clams is abundant and can reach 1 ton/day when the condition of the clams is declining. Based on this number, until now green mussels are only used for their meat to be consumed by the community and the waste accumulates in landfills and causes an unhealthy environment for the surrounding community. Based on this background, as an effort to reduce green clam shell waste, improvements need to be made. The purpose of this study is to be able to determine the optimal formulation/composition of green clam shell powder in the manufacture of bricks and to determine the characteristics/properties of bricks produced through testing rules. The method used in this study is an experimental method, carried out by making samples, testing samples, and drawing conclusions with comparative techniques against standards. The results obtained in this study are the optimal composition to produce good quality bricks, namely by using a mixture of 10% fine shell powder on sand. The characteristics or properties of the resulting bricks are with a compressive strength value of 10.26 N/mm2, water absorption of 16.45%, and resistance to nails (not broken or cracked)